Influences of internal and external inflationary features to the unemployed of Katuparan and Tondominium in Tondo, Manila - Abadicio, Charles Darwin M.; Asis, Bernadette P.; Ceballos, Princess D.; Daag, Czarina Mae S.; Dalena, Grace Anne S.; Dioco, Janica Keith R.; Francisco, Sophia Marie E.; Panahon, John Paul M.; Sese, Ann Lisette F.; Tolentino, Kaye T.; Velarde, Jarvin S. 4 0 16; 5
ABSTRACT: The study focused on the internal and external impact of inflation to the unemployed of Tondominium and Katuparan in Tondo, Manila. Since inflation rate is an alarming trend that should be focused on nowadays, it is long overdue that the Philippine government provide a concrete solution, a stable and consistent one at best. The researchers picked Katuparan and Tondominium in Tondo, Manila residents as their scope for this study because poverty slightly stricken those areas. The researchers gathered data through survey questionnaires and through qualitative interviews to help understand the effects of inflation to said locations. The researchers will conduct various analysis tools to the data that will be gathered to specifically understand the effects at all. All respondents to this study were informed on their rights to confidentiality of information and their data privacy act of 2012.
Business Research: (BSBA major in Business Economics and Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2